Information and Communication Technology and the Social Inclusion of Refugees1 - Andrade, Antonio Díaz; Doolin, Bill (MIS Quarterly, 2016)
The social inclusion of newly resettled refugees is a significant issue confronting both refugees and their host societies. Information and communication technologies (ICTs) are increasingly viewed as a useful resource in programs that provide settlement services or promote participation in society. This paper moves beyond the conventional discussion on the digital divide to explore what people are actually able to do and achieve with ICTs. We draw on an analysis of the use of ICTs for particular purposes by more than 50 resettled refugees to develop an explanation of the process by which ICT use contributes to their social inclusion. We propose that ICT constitutes a resource from which a set of five valuable capabilities is derived: to participate in an information society, to communicate effectively, to understand a new society, to be socially connected, and to express a cultural identity. In realizing these capabilities through ICT use, refugees exercise their agency and enhance their well-being in ways that assist them to function effectively in a new society and regain control over their disrupted lives.